A contemporary update on cancer and takotsubo syndrome - Tini, Giacomo; Arcari, Luca; Mistrulli, Raffaella; Follesa, Federico; Cianca, Alessandro; Sclafani, Matteo; Tocci, Giuliano; Spallarossa, Paolo; Battistoni, Allegra; Cacciotti, Luca; Musumeci, Beatrice; Barbato, Emanuele (Frontiers in Cardiovascular Medicine, 2024)
Takotsubo syndrome (TTS) is characterized by a transient left ventricular systolic dysfunction, burdened by significant acute and long-term mortality and morbidity. The prognosis of TTS, especially in the long-term, is influenced by both non-cardiovascular (non-CV) and CV comorbidities, among which cancer is one of the most common. The presence of a malignancy is proven to be associated with higher mortality in TTS. Moreover, a number of anticancer treatments has been reported to possibly cause TTS as a form of cardiotoxicity, even though clearcut associations are lacking. The aim of this narrative review is to sum up contemporary knowledge on the association of cancer and TTS, addressing unmet needs and practical implications. The importance of a close collaboration between cardiologists and oncologists is herein highlighted, both to allow an adequate management of the acute TTS phase, and to actively and safely return to the oncologic management once the acute setting is resolved.